German "volkstümliche Musik" of the Early Nineties and "Modern Society": Strategies of De-Individualisation as a Contribution to a Collective Re-Organisation (Schriften zur Kultur- und Mediensemiotik | Online, 2015)
"Volkstümliche Musik" is a significant phenomenon (at least) of the early 1990s. The analysis of this phenomenon can paradigmatically represent the discursive practices and sub-thought systems of large parts of the population of the Federal Republic of Germany at this time. "Volkstümliche Musik" depends on the political situation and indirectly deals with the needs and problems of individuals which result from such a situation and which lie in the deep structure of their mentalities. It thus takes on a cultural function.